Case report: Early use of whole exome sequencing unveils HNRNPU-related neurodevelopmental disorder and answers additional clinical questions through reanalysis - Dreikorn, Erika Nicole; Munro, Christine; Robin Berman, Natasha; Kunovac, Amina; Bellissimo, Daniel; Massart, Mylynda B. (Frontiers in Genetics, 2024)
This case report chronicles the diagnostic odyssey and resolution of a 27-year-old female with a complex neurodevelopmental disorder (NDD) using Whole Exome Sequencing (WES). The patient presented to a precision medicine clinic with multiple diagnoses including intellectual disability, autism spectrum disorder (ASD), obsessive-compulsive disorder (OCD), tics, seizures, and pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS). Although this patient previously had chromosomal microarray and several single-gene tests, the underlying cause of this patient's symptoms remained elusive. WES revealed a pathogenic missense mutation in the HNRNPU gene, associated with HNRNPU-related neurodevelopmental disorder (HNRNPU-NDD) and developmental and epileptic encephalopathy-54 (DEE54, OMIM: # 617391). Following this diagnoses, other treating clinicians identified additional indications for genetic testing, however, as the WES data was readily available, the clinical team was able to re-analyze the WES data to address their inquiries without requiring additional tests. This emphasizes the pivotal role of WES in expediting diagnoses, reducing costs, and providing ongoing clinical utility throughout a patient's life. Accessible WES data in primary care settings can enhance patient care by informing future genetic inquiries, enhancing coordination of care, and facilitating precision medicine interventions, thereby mitigating the burden on families and the healthcare system.